Implementation of BPI Framework Towards Business Process Analysis of TMint Creative Studio Malang Using Critical Success Factors - Fikri, Ahmad Fardan Salman; Wahyudi, Farid; Ratnasari, Novia (Proceedings of International Conference of Graduate School on Sustainability, 2026)
The rapid development of the digital creative industry requires companies to adopt efficient, adaptive business processes. TMint Creative Studio Malang, as a digital design service provider, faces challenges in optimizing workflows that impact team performance and service quality. This study aims to analyze and improve the company's business processes by applying the Business Process Improvement (BPI) framework using the Critical Success Factors (CSF) approach. The method used is a qualitative case study, with data collected through observation, interviews, and documentation. The analysis is based on the three main stages of BPI: organizing for improvement, understanding the process, and streamlining. The research results identified six main business processes, with two critical processes, website design production and social media management, selected through CSF analysis. The As-is modeling revealed inefficiencies in the workflow, which were then improved through the design of the To-be model using BPMN. Simulations showed increased time efficiency and reduced workload after the improvements were implemented. This study contributes to the development of more effective and efficient business processes in the digital creative industry.